Meningkatkan Penguasan Kosakata Bahasa Inggris Melalui Penggunaan Flashcard Interaktif pada Siswa Kelas Rendah di SDN 3 Jagaraga - Kadek Devy Marleni; Putu Windi Ridayanti Windi (ITP Markandeya Bali, 2026)
English language learning is one of the subjects taught at the elementary school level. This subject is introduced from Grade 1 to Grade 6. At this level, vocabulary mastery is an essential aspect that needs to be emphasized. A strong vocabulary foundation greatly assists students in understanding learning materials as well as improving their speaking and writing skills in English. However, in practice, there are several challenges faced by both students and teachers in vocabulary learning, one of which is the use of instructional media. The lack of appropriate teaching media significantly affects students’ interest and motivation in learning. Therefore, it is necessary to provide varied instructional media, one of which is interactive flashcards. Interactive flashcards are learning tools that integrate images, audio, and text. The use of interactive flashcards combines visual elements, game-based activities, and hands-on learning experiences that are suitable for the characteristics of young learners. Consequently, this learning medium can enhance students’ vocabulary mastery. The data collection methods employed in this study included interviews and direct classroom observations. The findings of this research indicate a significant improvement in the vocabulary mastery of lower-grade elementary students. Students were able to pronounce vocabulary accurately and recall the meanings of the words being asked.